PRODUCT VERSUS PROCESS WRITING APPROACH IN ESL WRITING CLASSROOM - Ainul Aqilah Aman; Hema Vanita Kesevan (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
This study compared the effects of practising product writing approach and process writing approach on ESL students’ writing ability. This was done in order to investigate on which writing approach was more suitable to be applied in ESL writing classroom as it played a crucial role in assisting the students to improve their writing abilities. In this study, 40 secondary school students were selected as participants and descriptive analysis was used to analyse the data. Participants of product writing approach (n=20) received traditional writing instruction while participants of process writing approach (n=20) were exposed to stages in writing. In this study, the effects of practising product and process writing approach were investigated by comparing the mean scores on the overall writing ability based on text content, communicative achievement, organisation, and language use. The findings indicate that there were no significant differences between the mean scores of students’ overall writing ability of process and product writing approach. Thus, instead of only focusing on either process or product writing approach solely while teaching ESL writing in Malaysian classroom, the findings from this study suggest teachers to combine both process and product writing approach in guiding the students to become independent writers.